A photostable triphenylamine-based flavonoid dye: Solvatochromism, aggregation-induced emission enhancement, fabrication of organic nanodots, and cell imaging applications. (July 2017) - Liu, Bin; Luo, Zijie; Si, Shufan; Zhou, Xianfeng; Pan, Chengjun; Wang, Lei
Abstract: Fluorescent organic nanodots are considered as the promising tools for long-term cellular imaging, due to their high luminescence, good photostability and good biocompatibility. In this study, a novel triphenylamine-based flavonoid dye with aggregation-induced emission enhancement characteristics was designed and synthesized. Based on these flavonoid dyes, the organic nanodots were facilely fabricated without further surface modification, exhibiting the low cytotoxicity, good resistance against photobleaching, and acceptable cell uptake. Remarkably, these nanodots achieved a long-term bioimaging for living cells with 70% of their initial fluorescence retained after 48 h continuously incubation. The excellent properties made the flavonoid dye the promising addition to the current library of fluorescent organic nanodots in bioimaging application. Graphical abstract: Highlights: The fluorescent flavonoid dye with aggregation-induced emission enhancement characteristic was firstly reported. The photophysical properties of fluorescent dyes including solvatochromism, AIEE, and photostability were carefully studied. The fluorescent nanodots based on AIEE flavonoid dyes were fabricated and applied for long-term cell imaging.